New insights into arginine and arginine-sparing effects of guanidinoacetic acid and citrulline in broiler diets. Issue 4 (2nd October 2021) - Dao, Hiep Thi; Swick, Robert A.
SUMMARY: Chickens have a high dietary Arg requirement compared to mammalians as they have an incomplete urea cycle and therefore cannot synthesise Arg. Arginine is important for protein synthesis and is also involved in immunity being converted to nitric oxide (NO) at the macrophage level. Nitric oxide is secreted as a free radical during an immune response and is toxic to bacteria, intracellular parasites and also has strong anti-viral and anti-cancer properties. Also, NO serves as a regulating factor for intestinal blood flow, integrity, secretion, and epithelial cell migration. As Arg is a limiting factor for NO synthesis, the increased availability of Arg following dietary supplementation of Arg and/or its metabolites could increase the NO production and subsequent immune status in birds. Such improvements on bird health may become useful for antibiotic growth promoter-free poultry production. The Arg requirement in birds has received special interest due to its large variation in different dietary conditions. Growing evidence suggests that increasing the dietary Arg level and Arg to Lys ratio above currently accepted levels may be necessary to maximise the productive potential of modern broiler strains due to the modulatory effect of Arg on energy and protein metabolism. Also, literature evidence has indicated that crystalline Arg, guanidinoacetic acid (GAA), and citrulline (Cit) can provide Arg activity in chicken diets and are all commercially available. Furthermore, the use of Cit could escape the degradation of enzyme arginase in the intestine and liver resulting in higher Arg levels in the bloodstream and NO production compared to Arg supplementation. The addition of GAA may also provide additional benefits on increasing creatine level and energy metabolism in broiler chickens compared to Arg. This paper will provide new insights into Arg and Arg-sparing effects of GAA and Cit in the broiler diets with a special focus on the supplementation of Arg in reduced protein diets.